Quantitative analysis of Robertsonian chromosomes inherited by descendants from multiple Rb heterozygotes of Mus m. Domesticus - Ayarza, Eliana; Cavada, Gabriel; Arévalo, Tamara; Molina, Alam; Berríos, Soledad (Frontiers in Cell and Developmental Biology, 2022)
Robertsonian (Rb) translocation is the most common chromosomal rearrangement in mammals, and represents the type of chromosomal change that most effectively contributes to speciation in natural populations. Rb translocations involve double-strand DNA breaks at the centromere level in two telocentric chromosomes, followed by repair ligation of the respective long arms, creating a metacentric Rb chromosome. Many different chromosomal races have been described in Mus musculus domesticus that show reduced chromosome numbers due to the presence of Rb metacentric chromosomes. The crossroads between ancestral telocentrics and the new metacentric chromosomes should be resolved in the meiotic cells of the heterozygote individuals, which form trivalents. The preferential segregation of metacentric chromosomes to the egg during female meiosis I has been proposed to favor their fixation and eventual conversion of a telocentric karyotype to a metacentric karyotype. This biased segregation, a form of meiotic drive, explains the karyotype changes in mammalian species that have accumulated Rb fusions. We studied and compared the number of Rb chromosomes inherited by the offspring of multiple Rb heterozygous of M. domesticus in reciprocal crosses. We did not find that the Rb chromosomes were inherited preferentially with respect to the telocentric chromosomes; therefore, we found no evidence for the meiotic drive, nor was there a random distribution of Rb chromosomes inherited by the descendants.